2020
DOI: 10.1186/s12957-020-01876-x
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of radical hysterectomy on endometrial cancer with cervical involvement?

Abstract: Background When endometrial carcinoma invades the cervical stroma, overall survival and disease-free survival decrease. However, it is still controversial whether patients in suspected stage II should be treated with radical hysterectomy. The goal of this study is to describe the role of radical hysterectomy in patients with endometrial carcinoma and cervical involvement. Methods This was a retrospective cohort study were a total of 239 patients with endometrial carcinoma with cervical involvement from Mexico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Japanese researchers believe that even if the tumor has invaded the cervix, RH is not necessary because it can improve the prognosis and lead to more perioperative and postoperative adverse events [11]. A North American study also discouraged RH for patients with stage EC because RH does not improve the patients' prognosis [12,13]. The results of this study indicate that neither PFS nor OS can be improved by RH/mRH and that PFS is worse in patients who undergo RH/mRH.…”
Section: Discussionmentioning
confidence: 85%
“…Japanese researchers believe that even if the tumor has invaded the cervix, RH is not necessary because it can improve the prognosis and lead to more perioperative and postoperative adverse events [11]. A North American study also discouraged RH for patients with stage EC because RH does not improve the patients' prognosis [12,13]. The results of this study indicate that neither PFS nor OS can be improved by RH/mRH and that PFS is worse in patients who undergo RH/mRH.…”
Section: Discussionmentioning
confidence: 85%
“…However, several clinical studies have reported contradictory results. 27,33 The type of hysterectomy was not identified as a prognostic factor in 180 EC patients; no survival benefits from RH were found and the procedure was more frequently associated with perioperative and urinary complications. 34 Phelippeau et al evaluated 7552 patients with stage II disease and found that the type of hysterectomy (RH) did not impact OS, even after adjusting for adjuvant radiation in a matched cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…However, several clinical studies have reported contradictory results 27,33 . The type of hysterectomy was not identified as a prognostic factor in 180 EC patients; no survival benefits from RH were found and the procedure was more frequently associated with perioperative and urinary complications 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of radical hysterectomy for women with FIGO 2009 stage II cancer of the endometrium has been controversial. Part of the published study has shown that the type of hysterectomy (radical hysterectomy versus simple hysterectomy) is not associated with the risk of disease recurrence and all-cause death in women with stage II cancer of the endometrium ( 14 16 , 26 28 ). However, there are also different viewpoints.…”
Section: Discussionmentioning
confidence: 99%
“…So we have this question: is a minimally invasive approach safe for stage II cancer of the endometrium which is also cervical involvement? In addition, in the treatment of stage II cancer of the endometrium, whether radical hysterectomy is oncologically superior to simple hysterectomy has not been determined ( 14 17 ).…”
Section: Introductionmentioning
confidence: 99%